3D study of temperature drop behavior of subsonic rarefied gas flow in microchannel. (3rd May 2018) - Shah, Niraj; Agrawal, Amit; Bhandarkar, Upendra
Abstract: 3D Numerical study of temperature variation for subsonic rarefied gas flow in a microchannel is carried out using an in-house MPI-based parallelized DSMC code. The temperature drop in the microchannel decreases with an increase in the aspect ratio whereas it increases with an increase in the pressure ratio, the cross-aspect ratio (CAR), and the Knudsen number. 3D and 2D simulations results are compared and effect of the CAR and Knudsen number are brought out. Finally, a correlation that predicts the temperature drop is formulated along with a list of conditions that ensures a near isothermal flow.